2013
DOI: 10.11118/actaun201260060287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early to late wood proportion on Norway spruce biomass

Abstract: Aboveground biomass, allometric relationships and early to late wood proportions were investigated in two even-aged monocultures of Norway spruce (Picea abies [L.] Karst) located at mountain and highland localities of the Czech Republic. However similar stand age and tree size, mountain trees comparing to them from highland showed less/tapering stems, lower aboveground biomass and lower stem wood density along the whole stem vertical profile as a result of different early to late wood proportion. These proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
3
5
0
Order By: Relevance
“…1 had the highest and lowest densities, respectively. On the other hand, mountain trees showed significantly lower stem wood density values compared to trees from lower altitude (Pokorný et al 2012). Gryc et al (2011) found that the average basic density was 576 kg/m 3 for spruce branch wood from different testing areas in the Czech Republic and that the mean stem basic density for the same testing areas was 430 kg/m 3 (it was 509.22 kg/m 3 in the present study).…”
Section: Density Variation In Spruce Woodsupporting
confidence: 51%
See 1 more Smart Citation
“…1 had the highest and lowest densities, respectively. On the other hand, mountain trees showed significantly lower stem wood density values compared to trees from lower altitude (Pokorný et al 2012). Gryc et al (2011) found that the average basic density was 576 kg/m 3 for spruce branch wood from different testing areas in the Czech Republic and that the mean stem basic density for the same testing areas was 430 kg/m 3 (it was 509.22 kg/m 3 in the present study).…”
Section: Density Variation In Spruce Woodsupporting
confidence: 51%
“…However, the same tree species of similar tree age can differ due to site-specific growing conditions including forest structure (Pokorný et al 2012). Additionally, within two even-aged monocultures of Norway spruce located at mountain and highland localities of the Czech Republic with similar stand age and tree size, mountain trees comparing to them from highland showed less/tapering stems and lower stem wood density as a result of different early to late wood proportion (Pokorný et al 2012;Jyske et al 2008). The spruce wood density varied with high statistical significance (P < 0.001) by location (Fig.…”
Section: Density Variation In Spruce Woodmentioning
confidence: 99%
“…in Bulgaria. In the Krkonose Mountains in the Czech Republic cold summers are the cause of small radial increments in the old growth spruce forests near the upper tree line (Sander et al, 1995), whilst elevated air temperature during summer time in highland region of this country stimulates latewood growth in Norway spruce (Pokorný et al, 2012b). Campelo et al (2006) reported no signifi cant positive relationship between precipitation in August and latewood formation in Stone pine Pinus pinea L. from a dry Mediterranean area in southern Portugal.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, late spring and entire growing season temperature infl uence the formation of light rings (rings that are light-colored due to incomplete latewood cell wall development) formation in black spruce at the tree line near bush lake, northern Québec (Yamaguchi et al, 1993). Pokorný et al (2012b) found that ample water supply during spring time in Beskydy Mts. (Czech Republic) supports earlywood formation in Norway spruce.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between wood density and temperature during the growing season is generally negative (Ivković et al 2013). Water availability is a limiting factor for earlywood (EW) development in the spring time, whereas low air temperature is restraining LW growth in the summer time (Pokorný et al 2012). According to Franceschini et al (2012), between-and within-ring variations are influenced by tree developmental stage, site, genetics, and forest management.…”
Section: Introductionmentioning
confidence: 99%